Design of Cardionics Stethoscopes and Bluetooth Wireless to Analyze Lung Sounds Using LabView Software - Destra Andika Pratama; RD Kusumanto; Akhmad Nurhanafi Alif (STMIK Budi Darma, 2023)
The lungs are organs in humans that run the respiratory system (breathing) and function as an exchange of oxygen and carbon dioxide. To detect lung sounds, a stethoscope is needed as a tool to listen to sounds in the lungs. This technique is commonly called auscultation. This article aims to modify the Cardionics digital stethoscope medical device by adding Bluetooth Wireless so that it can be recorded in a software program called LabView. The sound produced from the Cardionics stethoscope is connected to a Bluetooth transmitter type, and the signal will be received by a Bluetooth receiver type that has been connected to MyRio. MyRio will then be connected to LabView software to display a graph of the Lung sound signal. This research will make it easier for doctors to analyze the patient's lung sounds.